Balanced and Unbalanced: Physical Proofs of the Mean Inequalities. Issue 1 (1st January 2023) - Edgar, Tom
Summary: We provide two visual proofs of the two-variable harmonic mean-geometric mean-arithmetic mean-quadratic mean inequalities: one using a center of mass model and one using moments of mass.